PKM Pengelolaan Keuangan Bagi Ibu Rumah Tangga - Hajrah Hamzah; Siti Nur Reskiyawati Said; Yulia Yunita Yusuf; Farhan Dwinanda Hanisyahputra; Nurul Rusdiansyah (Lembaga Pengembangan Kinerja Dosen, 2026)
Family financial management is a crucial aspect of maintaining household stability and well-being. However, many housewives still do not systematically record their finances, resulting in frequent imbalances between income and expenses. This community service activity aims to improve the understanding and skills of housewives in preparing simple financial reports as an effort to manage family finances more planned and controlled. The target group for this activity was 30 housewives in Pesantren Nurus Sunnah Bulukumba Regency who act as family financial managers. The implementation method included outreach, material delivery, practical training on preparing simple financial reports based on cash flow recording, as well as mentoring and evaluation. The results of the activity showed high enthusiasm for the training and a growing understanding of the importance of recording household income and expenses. Based on the evaluation, approximately 80% of participants understood the benefits of preparing family financial reports and began to apply them in their daily lives, while approximately 20% of participants still needed further mentoring. Thus, this training activity was able to improve financial literacy and encourage behavioral changes in more disciplined and planned family financial management.